The ACE (Albumin, CRP and Endoscopy) Index in Acute Colitis: A Simple Clinical Index on Admission that Predicts Outcome in Patients With Acute Ulcerative Colitis. Issue 4 (23rd June 2020) - Grant, Rebecca K; Jones, Gareth-Rhys; Plevris, Nikolas; Lynch, Ruairi W; Jenkinson, Philip W; Lees, Charlie W; Manship, Thomas A; Jagger, Fiona A M; Brindle, William M; Shivakumar, Mrithula; Satsangi, Jack; Arnott, Ian D R
Abstract: Background: Intravenous (IV) steroids remain the first-line treatment for patients with acute ulcerative colitis (UC). However, 30% of patients do not respond to steroids, requiring second-line therapy and/or surgery. There are no existing indices that allow physicians to predict steroid nonresponse at admission. We aimed to determine if admission biochemical and endoscopic values could predict response to IV steroids. Methods: All admissions for acute UC (ICD-10 K51) between November 1, 2011, and October 31, 2016 were identified. Case note review confirmed diagnosis; clinical, endoscopic, and laboratory data were collected. Steroid response was defined as discharge home with no further therapy for active UC. Nonresponse was defined as requirement for second-line therapy or surgery. Univariate and binary logistic regression analyses were employed to identify factors associated with steroid nonresponse. Results: Two hundred and thirty-five acute UC admissions were identified, comprising both acute severe and acute nonsevere UC; 155 of the 235 patients (66.0%) responded to steroids. Admission C-reactive protein (CRP) ( P = 0.009, odds ratio [OR] 1.006), albumin ( P < 0.001, OR 0.894) and endoscopic severity ( P < 0.001, OR 3.166) differed significantly between responders and nonresponders. A simple UC severity score (area under the curve [AUC] 0.754, P < 0.001) was derived from these variables; 78.1% (25 of 32) of patients with concurrent CRP ≥50 mg/L, albumin ≤30 g/L, and increased endoscopic severity (severe on physician's global assessment) (maximum score = 3) did not respond to IV steroids (positive predictive value [PPV] 78.1%, negative predictive value [NPV] 87.1%). Conclusions: More than three quarters of patients scoring 3 (albumin ≤30 g/L, CRP ≥50 mg/L, and increased endoscopic severity) did not respond to IV steroids. This combination of parameters (ACE) identifies on admission a high-risk population who may benefit from earlier second-line medical treatment or surgical intervention.